Neurodevelopmental status of Severe Acute Malnutrition children of 6 months to 59 months and its follow-up at 6 months using Trivandrum Developmental Screening Chart (TDSC) - Satyala, Ravi Teja; Kumar, Arun; SOMAN, ADARSH; Raul, Saswat ranjan (Indian Journal of Child Health, 2026)
Background: Malnutrition has a significant impact on the neurodevelopment of Children. Toddlers, especially those below 24 months, are more prone to malnutrition and neurodevelopmental delay. Once neurodevelopmental delay develops, there will not be much improvement even after treatment or rehabilitation. The nutritional status of severe acute malnutrition (SAM) children can be reverted to normal by proper management, rehabilitation, following advice, and with regular follow-up. This study was done to assess the neuro-developmental delay in SAM children at the time of diagnosis and their follow-up after six months to assess the level of recovery, if any, after the treatment using the Trivandrum Developmental Screening Chart (TDSC). Materials and Methods: A total of 103 children were assessed for any delay in development using TDSC at the time of diagnosis and after 6 months from the diagnosis, post-rehabilitation and treatment. The chronological and developmental ages were measured and marked at both intervals, which, on analysis, gave the developmental delay for that corresponding age if present. Results: Of 103 children, 47 (45.6%) identified as having developmental delay using the TDS chart. The highest number of children with neurodevelopmental delay (38 out of 47, i.e., 80.9%) was observed in the 6-24-month age group, which decreased to 32 (82.1%) at the 6-month follow-up. Among children aged > 24 months, 9 (19.1%) participants had Neurodevelopmental delay, while at follow-up, only 2 recovered, and 7 (17.9%) were found to have neurodevelopmental delay even after treatment and rehabilitation. Conclusion: The results show that once neurodevelopmental delay develops due to malnutrition during a vulnerable period, it will not improve even after treatment or rehabilitation.